Potencial de produção de energia a partir da biometanização de resíduos orgânicos do Câmpus Pampulha da UFMG - Júlia Nunes Costa Gomes (2014)
The search for new integrated waste management strategies will be one of the great movements in Brazil in accordance with the National Policy on Solid Waste, instituted by Law n° 12.305/2010. The aim of this study was to evaluate the power generation potential from the biomethanation of organic waste generated at the Pampulha campus. Food scraps, non-recyclable paper (napkins and paper towels) and yard waste (grass clipping and leaves) were chosen because of significant generation on campus. Initially, an inventory of the wastes generation was conducted from August 2011 to July 2012. The data show that the generation of food waste was not related to the way the meal is sold (self-service, dish-made and university cafeteria). Furthermore, it was found that the consumption of paper napkins and paper towel per person per meal was high and it can be seen as a point of awareness campaigns to reduce the generation at the source. The population equivalent of generating organic waste by campus was approximately 2600 inhabitants (annual average) and about 4700 inhabitants (average critical month). The quantitative and type variation of organic waste was very expressive, thus the combination of biomethanation and composting techniques enable the management of waste with energy recovery for purposes of internal use and plataform study. The biomethanation potential of campus residues was assessed by anaerobic co-digestion assays representing the variation in the proportion of monthly waste generation. The best results of CH4 specific production (mLCH4.gSTVresidues-1) were associated with higher content of restaurant waste (food waste, paper napkins and paper towels) samples, which are easily degradable. Intermediate results were associated with low levels of restaurant residues and high levels of grass pruning, whereas the worst results associated with low levels of restaurant residues and high levels of dry leaves. Extrapolating data from CH4 specific production to monthly waste generation in the period analysed, the potential for monthly electricity generation was approximately 7400-29000 kWh. This energy potential emerges as the great interest to the UFMG mainly to attenuate the consumption in higher tax periods.